(3eNJUQ TQM HMQb Ydi dGejI GHf eGdc aj GdUQas - (3YHO Gddg NGdOs ((3eMeO Hf eMeO GdMhJs)
(3ChdgG (B:s
(3GdMeO ddg hcai, hUdGI hSdGe Ydi YHGOg GdPjf GUWai hHYO ajbhd GdYHO GdabjQ cKjQ GdPfhH hGdJbUjQ YHO Gddg NGdO gPG eNJUQ aj Yde GdUQa jJYdb HHjGf eYGfj GdefXheI GddGejI ddEeGe GdLdjd GHf eGdc eCNhP ef TQMgG GdeTghQ TQM HMQbs
(3BNQgG (B:s
(3hGdhLg GdHGSQ hGdYjGP HGddg gh GdWGdM hefg hhLhg (B((3jheFP(B) (3HGSQI hGdhLd GdNGFa , Mbb Gddg eG QLGg hCYGPg eeG jNTGg hGSJLGH dg eG OYGg Bejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdUQas